Analisis Sintaksis: Jenis Frasa pada Lirik Lagu Rony Parulian dalam Album "Rahasia Pertama" - Nadia Putri Nabhila; Fadhilatur Rosyidah; Erfina Rahayu; Ahmad Faizi; Icha Fadhilasari (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This study aims to analyze the syntactic structure in Rony Parulian's song lyrics on the album "Rahasia Pertama", focusing on seven types of phrases, namely nominal phrases, verbs, adjectives, adverbs, numerals, prepositions, and conjunctions. The method used is a descriptive qualitative approach with text analysis techniques to identify and classify phrases based on their syntactic forms and functions. The results of the study show that all types of phrases are found in song lyrics and have functions as subjects, predicates, objects, complements, and adverbs. The use of phrases not only builds grammatical sentence structures, but also strengthens the emotional, aesthetic, and expressive meanings in the lyrics. These findings confirm that the power of language in songs lies in the syntactic structure that is able to convey messages deeply and poetically.